The correct answer is option 2.
3 = 0
x - a = 0
x = a
x + b = 0
x = -b
We do not multiply any of these values by 3 because in a way, 3 is acting as another "zero" of the equation. Though, as shown above, it does not equal 0, it still does not apply to any of the other equations solved above.
Hope this helps!! :)
Answer:
a² + 4ab + 4b²
Step-by-step explanation:
Given
(a + 2b)²
= (a + 2b)(a + 2b)
Each term in the second factor is multiplied by each term in the first factor, that is
a(a + 2b) + 2b(a + 2b) ← distribute both parenthesis
= a² + 2ab + 2ab + 4b² ← collect like terms
= a² + 4ab + 4b²
Answer: See each part below.
1) A, B, and C are the coefficients in order when it equals 0. Move over the 4 and you have 5, 9, -4 or Choice B.
3) If you graph the equation, it will be above the x-axis. Therefore, it has no roots. Choice D
4) Choice A is correct. Use the coefficients: A = 4, B = 3, C = -10. Simply plug those into the quadratic equation and you will get -2 and 1.25.
Answer:
56
Step-by-step explanation:
8 times 7=56